2013
DOI: 10.1097/md.0b013e31827f6104
|View full text |Cite
|
Sign up to set email alerts
|

Community-Acquired Legionella pneumophila Pneumonia

Abstract: Legionella pneumophila has been increasingly recognized as a cause of community-acquired pneumonia (CAP) and an important public health problem worldwide. We conducted the present study to assess trends in epidemiology, diagnosis, clinical features, treatment, and outcomes of sporadic community-acquired L. pneumophila pneumonia requiring hospitalization at a university hospital over a 15-year period (1995–2010). Among 3934 nonimmunosuppressed hospitalized patients with CAP, 214 (5.4%) had L. pneumophila pneumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(39 citation statements)
references
References 40 publications
4
34
1
Order By: Relevance
“…However, clinical and laboratory parameters have shown low sensitivity and/or specificity. Although our understanding of CAP caused by Legionella has improved substantially in recent years due to new diagnostic and treatment strategies, a recent study conducted by our group [26] showed that 11.2% patients with LP received inappropriate empirical antibiotic therapy at hospital admission. However, the overall proportion of patients who received inappropriate empirical antibiotic therapy at hospital admission remained stable over the years (from 1995 through 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical and laboratory parameters have shown low sensitivity and/or specificity. Although our understanding of CAP caused by Legionella has improved substantially in recent years due to new diagnostic and treatment strategies, a recent study conducted by our group [26] showed that 11.2% patients with LP received inappropriate empirical antibiotic therapy at hospital admission. However, the overall proportion of patients who received inappropriate empirical antibiotic therapy at hospital admission remained stable over the years (from 1995 through 2010).…”
Section: Discussionmentioning
confidence: 99%
“…(10,(137)(138)(139). In addition, despite the sensitivity of L. pneumophila to commonly available antibiotics, LD is associated with greater CAP severity and a higher case-fatality rate (up to ϳ30%) than CAP from other atypical pathogens (121,(140)(141)(142)(143)(144)(145). The U.S. LD case-fatality rate has decreased steadily since the mid-1980s (125), from a high of ϳ34% to 8% on average in the 2000s (15).…”
Section: Epidemiology and Diseasementioning
confidence: 99%
“…The UAT has dramatically outpaced other laboratory methods for diagnosis, representing 82% and 97% of the diagnostic tools used for LD confirmation in Europe and the United States, respectively (15,125,144,146,257). The popularity and ubiquity of the UAT are attributed to its speed, relatively low cost, uncomplicated procedure, ease of sample collection, commercial availability, and FDA clearance (CE marking in the European Union).…”
Section: Urinary Antigen Testmentioning
confidence: 99%
“…The first pathogen, L . pneumophila , infects lung macrophages and remains confined to the lung [45,47,48] [46,75], while the second pathogen S . pyogenes spreads systemically [67] [35] [68] [69].…”
Section: Discussionmentioning
confidence: 99%
“…pneumophila infection remains confined to the lung under most circumstances where it causes a severe pneumonia [45] [46]. This bacteria is found in contaminated water supplies, such as air-conditioning systems, and infects alveolar macrophages [45,47,48] [46]. It can cause complications in people with immunosuppression or other health problems, making it an important hospital-acquired infection [49] [50].…”
Section: Introductionmentioning
confidence: 99%